Bioaktivitas dan Efek Kesehatan Bawang Hitam terhadap Enzim Reduktase Hidroksi Metilglutaril-KoA Pada Tikus Putih Jantan Obesitas - Ibrahim, Ibrahim; Yerizel , Eti; Endrinaldi, Endrinaldi; Revilla, Gusti (Journal of Pharmaceutical and Sciences, 2025)
Obesity is a condition of abnormality or excess fat accumulation in adipose tissue. HMG-CoA reductase is an enzyme that can catalyse HMG-CoA into mevalonate, which is needed in cholesterol biosynthesis. Inhibition of the HMG-CoA reductase enzyme is an effective drug target mechanism to overcome dyslipidemia. Black garlic, which is high in antioxidants such as SAC, flavonoids, and polyphenols, is an effective mechanism. This study tested the bioactivity and health effects of black garlic on the activity of HMG-CoA reductase enzyme. This type of experimental study on male rats uses a post-test control-only group design. The sample in this study was 25 experimental animals divided into five groups, group negative control with a regular diet, group positive control with a high-fat diet, group treatment 1 with a high-fat diet and black garlic dose of 200 mg/rats, group treatment 2 with a high-fat and black garlic diet dose of 400 mg/rats, and group treatment given a high-fat diet and black garlic dose of 800 mg/rats. The results of the study showed that the average value and standard deviation of HMG-CoA in the negative control group were 1,044 and 0.088, the positive control group 2,136 and 0.487, the 1 group treatment 1,292 and 0.194, the 2 group treatment 1,296 and 0.206 and the three treatment group 1,201 and 0.201 nmol/min/mg protein. Based on the results of the hypothesis test, the significance level for the five groups was 0.004, indicating a significant difference in the average HMG-CoA levels in groups K1, K2, P1, P2, and P3. Black garlic significantly decreased HMG-CoA reductase activity in rats fed a high-fat diet, supporting its potential as a natural therapeutic agent for dyslipidemia management.